Capítulo III: La mujer: Realidad y fantasía en los cuentos. - Lira, Gloria Gálvez (María Luisa Bombal: Realidad y Fantasía, 1986)
The book "María Luisa Bombal: Realidad y Fantasía," written by Gloria Gálvez Lira and published by Scripta Humanistica in 1986 is presented. It offers the author's dissertation which explores the narrative fiction of Chilean author María Luisa Bombal and its depiction of women, fantasy and reality in the historical and socio-economic context of 20 century Chile.